Social and culture study of Israel and Egypt. - Cheng, Kok Keong. (2008)
This dissertation describes the social and cultural environments that are important to doing business in Egypt and Israel. It highlights various businesses and religious customs as well as the social etiquette that are unique in each of the countries. Other aspect of the social and political issues like overpopulation, housing, the constant threat of war as well as terrorism are also discussed to further our insights into the dynamic changes that are taking place within these two countries. Contemporary issues like entrepreneurship in high tech startups are also mentioned for a better understanding of the changing lifestyles in the new economy and Internet age.